Peranan Pusat Informasi Pariwisata (TIC) dalam Memberikan Layanan Informasi Pariwisata Kota Ternate - Muslim Fadel; Nur Fajrhi; Imelda Rahman; Nariyah Tafrijiyah Wardhani Abdul Haris (Yayasan Literasi Sains Indonesia, 2025)
The Tourism Information Center plays a very important role and serves as a supporting facility in promoting the tourist attractions and destinations of a particular region. With the existence of a Tourism Information Center in an area, tourists will not have difficulty and can easily obtain information related to tourism in that region. It has a very significant role in introducing tourist attractions to visitors; therefore, it requires excellent and professional service to ensure that tourists are not disappointed when seeking tourism information. The purpose of this study is to determine the role of the Tourism Information Center in providing tourism information services in Ternate City. The method used in this research is a qualitative approach, which involves key efforts such as posing questions and procedures, collecting specific data from participants, analyzing the data inductively from specific themes to general themes, and interpreting the data. The results of the study show that the role of the Tourism Information Center in Ternate City has not been carried out optimally due to limited budgets and a lack of human resources with competence in the field, which has caused the Tourism Information Center in Ternate City to often not operate during working hours.